Endoscopic features of non-IBD colitis - Pigò, Flavia; Reggiani Bonetti Luca; Conigliaro Rita (Asian Journal of Medical Sciences, 2023)
Background: Studies about the endoscopic aspect of non-inflammatory bowel disease (IBD) colitis are scarce. Aims and Objectives: The aim of this retrospective study was to describe the endoscopic appearance of non-IBD colitis (NIC) in an outpatient cohort. Materials and Methods: All cases of NIC, from 2018 to 2021, with a recent outpatient colonoscopy, were enrolled. Diagnosis was based on clinical, endoscopic, and histological characteristics, and follow-up ≥6 months to recognize misdiagnosed IBD because of mimic causes. Results: 158 patients (63 males, age 54 years±19) performed a colonoscopy with a final diagnosis of NIC associated with drug-exposition (74), food allergies (26), recent/active gastrointestinal infections (20), ischemic colitis (14), segmental colitis associated diverticulosis (SCAD) (10), obstructed defecation syndrome (ODS) (8) and microscopic colitis (6). Frequencies of endoscopic features and colon distribution were: Drug exposition (hyperemia, erosions/ulcers, 88%; right colon, 70%), recent infection (erosions, 60%; left colon/rectum, 88%), food allergies (red spots/erosions, 67%; all the colon), ischemic colitis (ulcers, 86%; right or left colon), SCAD (hyperemia/edema, 75%; always left colon), ODS (hyperemia, erosions, and loss of vascularity, 90%; always rectum), microscopic colitis (edema and hyperemia; all the colon). Conclusion: Drug-exposition is the most frequent cause of out-patient NIC. In an appropriate diagnostic context, red spots, hyperemia, and erosions are associated with drug expositions, recent infections, and food allergies. Ulcers are more frequent with ischemic colitis or drug-exposition.